Integrated effort in the prioritization of areas of conservation in Borneo - Das, Indraneil; Kueh, Boon-Hee; Maryati, Mohamed; Chew, Danny (2004)
Prioritization of areas has become a crucial aspect of environmental conservation. Prioritization of areas for conservation reviews areas with the best representation of biodiversity so that conservation efforts, and especially the scarce conservation money, can be targeted for effective and feasible environmental conservation. This is even so when human-induced environmental disturbances and threats such as deforestation, logging, pollutions, forest fire, flood, and poaching are intensifying rapidly over the years exerting overwhelming pressure on the environment. For instance, the coverage of undisturbed forest (lowland and highland Dipterocarp forest) in Sabah has dropped 85.25% from 1975 to 1992 (Ministry of Science, Technology and the Environment, Malaysia, 1997). These disturbances and threats have direct link with anthropogenic activities for economic gains like agriculture (Ooi, 1993), industrialization and housing. Consequently, the competition for land between materialistic development and conservation stiffens. Sacrifice of the former for the latter and vice versa are unrealistic. Thus, compromise is inevitable; prioritization of areas for conservation has become important.